Investigating Tourist Satisfaction: The Impact of Tourism Facilities and Service Quality in Mapak City, Ivory Coast - Ropiqi, Ahmad (Advances in Tourism Studies, 2025)
ABSTRACTThis research discusses the influence of tourist facilities, service quality, andTourist Satisfaction in Ivory Coast Mapak.Ivory Coast is at the western tip ofMataram City, precisely in the Mapak Indah neighborhood, Jempong Baru Village,Sekarbela District, Mataram City.The aim of this research is to determine whetheror not there is an influence on tourist facilities and service quality on touristsatisfaction in Ivory Coast Mapak Mataram City. Study This is a quantitativedescriptive research using analytical techniques data, namely multiple linearregression analysis. Data collection was carried out by observation,documentation, and questionnaires. The sample in this study was 79 respondentswith techniquespurposive sampling. The research results show that Touristsatisfaction will be influenced by the independent variable, namely tourist facilities(X1), and service quality (X2) of 52.8%, while the remaining 42.2% will beinfluenced by other variables that have not been studied in depth pthis research.